The Iowa Gambling Task in Violent and Nonviolent Incarcerated Male Adolescents - Umbach, Rebecca (Criminal justice and behavior, 2019)
Previous studies have found impaired affective decision-making, as measured by the Iowa Gambling Task (IGT), in various antisocial populations. This is the first study to compare the IGT in violent and nonviolent incarcerated American youth. The IGT was administered to 185 incarcerated adolescent male offenders charged with either nonviolent (38.4%) or violent (61.6%) crimes. General linear mixed models and t tests were used to assess differences between the groups. The full sample performed worse than if they had selected from the decks at random. The violent offenders performed more poorly than the nonviolent offenders overall, primarily because they preferred “disadvantageous” Deck B to a greater degree; however, they did demonstrate some degree of learning by the final block of the task. Adolescent offenders demonstrate impaired affective decision-making. Behavior suggested preferential attention to frequency of loss and amount of gain and inattention to amount of loss.